Evaluation of potential early life risk factors for ulcerative colitis - Gökden, Yasemin; Ogutmen Koc, Deniz (Journal of Surgery and Medicine, 2020)
Aim: It has been suggested that early life factors may affect the risk of inflammatory bowel disease by affecting the gut microbiome. Delivery type, breast milk, and parental smoking are the most important environmental factors. There are limited studies on the effects of these factors on the location of the disease and age at diagnosis. In addition, the effects of these factors on medical treatments and bowel involvement are unknown. We examined the relationship between potential early-life risk factors experienced in the first years of life and ulcerative colitis (UC). Material and Method: This study is a prospective case-control study. Sixty-nine UC patients were compared with 44 age- and sex-matched healthy controls (HC). We investigated delivery type, breastfeeding, maternal age at birth, and parents’ smoking status, which may be potential early-life risk factors. Our analysis involved the relationship of these potential factors with the age at diagnosis and medical treatments in UC patients. Results: UC and HC groups were compared in terms of delivery type, breastfeeding, and parents’ smoking status: There was no statistical difference between the groups. In terms of the duration of breastfeeding, we found that 6-12 months of breastfeeding was lower in the UC group (P=0.046). In addition, the age at diagnosis of the disease was lower in UC patients who were not breastfed and whose mothers smoked (P=0.031, P=0.016, respectively). Conclusions: The duration of breastfeeding is important for the development of UC. We recommend breastfeeding for longer than six months to prevent UC. Maternal smoking cessation has a protective role in the risk of early-onset UC.